Preparation method of polymer glue for diaphragm coating, polymer glue, diaphragm and battery
By using polymer glue, its core includes a base core and an elastic structure that penetrates the pores on the surface of the base core, it solves the problem that the ceramic coating is difficult to release stress and easily lose powder, improves the battery's magnification and cycling performance, and ensures the long-lasting bond strength of the ceramic coating to the electrode sheet.
Patent Information
- Application Number
- CN202510252003.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-05
AI Technical Summary
The existing ceramic coatings are difficult to release stress and easily lose powder. The adhesive easily fills the ceramic gaps and separator pores, affecting the battery's magnification and cycling performance.
Polymer glue is used, which includes polymer particles. The particle core includes a base core and an elastic structure. The base core has at least a hole on the surface. The elastic structure penetrates the surface pores of the base core. The shell covers the core. The PDI of the polymer particles is <1, D50 is 1μm~11μm, the glass transition temperature of the base core material is not less than 50℃, the elastic modulus of the elastic structure material is 10MPa~80MPa, the shell material is hot pressed under 55℃ and 4MPa conditions, and the adhesion force to the electrode sheet is not less than 5N/m.
This polymer glue can avoid filling the gaps between ceramic particles and separator pores, reduce the internal resistance of conductive ions, and improve the battery's magnification and cycling performance. The ceramic coating can fully release stress during the battery ion de-embedding process, ensuring that the anti-electrode sheet has a long-lasting bonding strength and does not easily lose powder.
Smart Images

Figure CN119735990A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery separators, and in particular, relates to a method for preparing a polymer glue for separator coating, a polymer glue, a separator and a battery. Background Art
[0002] At present, the lithium-ion battery separators used commercially are mainly polyolefin material separators with good acid and alkali resistance, high tensile strength and pores. However, this type of separator is easy to shrink at high temperatures, which may cause the positive and negative electrodes of the battery to directly contact, causing internal short circuits and spontaneous combustion or explosion, posing a great safety hazard. In addition, the surface energy tension of polyolefin separators is low and it is difficult to be wetted by electrolytes, which to a certain extent hinders the penetration of lithium ions, resulting in low battery capacity and seriously affecting its performance.
[0003] It has been proposed that a ceramic heat-resistant coating be applied on one or both sides of a polyolefin or other diaphragm. On the one hand, this can effectively reduce the thermal shrinkage of the diaphragm and prevent fire and explosion caused by short circuits between the positive and negative electrodes when the battery is at high temperature. At the same time, the ceramic coating can also improve the wettability of the diaphragm to the electrolyte. However, the coating of ceramic inorganic particles must be assisted by a binder to have good adhesion, and the existing binders easily fill the ceramic gaps and diaphragm pores, resulting in an increase in the internal resistance of lithium ions, and affecting the rate and cycle performance of the battery. In addition, the existing ceramic coating is difficult to release stress when the volume changes during the battery de-lithiation and insertion process, and the ceramic coating is prone to powdering.
[0004] It should be noted that this part of the present invention only provides background technology related to the present invention and does not necessarily constitute prior art or known technology. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of existing ceramic coatings that it is difficult to release stress, the ceramic coating is easy to shed powder, and the ceramic coating binder is easy to fill the ceramic gaps and the pores of the diaphragm, affecting the rate and cycle performance of the battery. A preparation method of a polymer glue for a diaphragm coating and a polymer glue, a diaphragm and a battery are provided. The polymer glue will not fill the ceramic particles and the pores of the diaphragm, and can improve the rate and cycle performance of the battery. The ceramic coating prepared by the polymer glue can fully release stress and is not easy to shed powder.
[0006] In order to achieve the above-mentioned purpose, in the first aspect, the present invention provides a polymer glue for diaphragm coating, which includes polymer particles, the polymer particles include an inner core and an outer shell, the inner core includes a base core and an elastic structure, the base core has holes on at least the surface, the elastic structure at least penetrates the holes on the surface of the base core, the outer shell is coated on the surface of the inner core, the PDI of the polymer particles is less than 1 and the D50 is 1μm~11μm, the glass transition temperature of the material of the base core is not less than 50°C, the elastic modulus of the material of the elastic structure is 10MPa~80MPa, and the material of the outer shell is hot pressed under the conditions of 55°C and 4MPa, and the bonding force to the electrode is not less than 5N / m.
[0007] In some preferred embodiments, the base core is a porous base core, and the elastic structure penetrates through the pores inside the porous base core.
[0008] In some preferred embodiments, in the inner core, the volume ratio of the elastic structure to the base core is 1:2.5-9.
[0009] In some preferred embodiments, in the polymer particles, the volume ratio of the shell to the core is 1:1.5-6.
[0010] In some preferred embodiments, the base core includes a polymer formed by polymerizing a base core monomer, and the base core monomer includes at least one monomer selected from the group consisting of an acrylic monomer and a vinyl monomer.
[0011] Preferably, the base core comprises polymethyl methacrylate.
[0012] In some preferred embodiments, the shell comprises a copolymer, and the copolymer is formed by copolymerization of a mixed monomer comprising a first shell monomer, a second shell monomer, and a third shell monomer, wherein the first shell monomer is selected from at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, lauryl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, and vinyl acetate, and the second shell monomer is selected from at least one of trifluoroethyl methacrylate, 2-hydroxyethyl methacrylate, and 1,2-difluoroethyl methacrylate. The present invention relates to a monomer comprising at least one of 1,2-dimethoxypropyltrimethoxysilane, 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, ethylene glycol diacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, glycidyl methacrylate, N-hydroxymethyl acrylamide, N-butoxymethyl acrylamide, divinylbenzene, vinyl trimethoxysilane, and γ-methacryloxypropyl trimethoxysilane, and the third shell monomer is selected from at least one of methyl methacrylate, ethyl methacrylate, methacrylic acid, acrylic acid, acrylonitrile, styrene, isobornyl methacrylate, and acrylamide.
[0013] In the second aspect, the present invention provides a method for preparing the polymer glue described in the first aspect, comprising: preparing a spherical base core precursor, the glass transition temperature of the material of the base core precursor is not less than 50°C, making holes on at least the surface of the base core precursor to obtain a base core, the base core at least has holes on the surface, so that an elastic material at least penetrates the holes on the surface of the base core to obtain an inner core, the elastic modulus of the elastic material is 10MPa~80MPa, coating the surface of the inner core with a viscous material to prepare a stable emulsion to obtain the polymer glue, the viscous material is hot pressed under the conditions of 55°C and 4MPa, and the bonding force to the electrode is not less than 5N / m.
[0014] In some preferred embodiments, the preparation of the base core comprises: emulsifying and mixing a mixture including the base core precursor, a porogen, a water-soluble monomer, an initiator, an emulsifier, and water, reacting under stirring conditions, washing with water, and solid-liquid separation to obtain the base core, the porogen is selected from at least one of cyclohexanol, toluene, xylene, benzene, acetone, isopropanol, ethyl acetate, and halogenated hydrocarbons, the water-soluble monomer is selected from at least one of acrylic acid, methacrylic acid, acrylamide, methacrylamide, N,N-dimethylacrylamide, and propenyl ether, the reaction temperature is 55° C. to 100° C., the reaction time is 2 h to 10 h, and the mass ratio of the base core precursor, the porogen, and the water-soluble monomer in the mixture is 1:0.01~0.27:0.01~0.45; The preparation of the inner core comprises: emulsifying and mixing a mixture comprising the base core, an elastic material, an emulsifier and water uniformly to obtain the inner core, wherein the mass ratio of the elastic material to the base core in the mixture is 1:1.5-12.
[0015] In some preferred embodiments, the preparation of the inner core comprises: emulsifying and mixing a mixture comprising the base core, an elastic material, an emulsifier and water to obtain the inner core, wherein the mass ratio of the elastic material to the base core in the mixture is 1:2.5-9.
[0016] In some preferred embodiments, the coating of the viscous material comprises: uniformly mixing a mixture including the core, an initiator, and a viscous material monomer, and coating the viscous material on the surface of the core by polymerization, wherein the mass ratio of the viscous material monomer to the base core is 1:1.5-6.
[0017] In some preferred embodiments, the preparation of the base core precursor includes: mixing a mixture including a dispersant, an emulsifier, a base core monomer, an initiator, and a cross-linking agent in water, and separating the solid and liquid after the reaction to obtain the base core precursor, wherein the cross-linking agent is selected from at least one of acrylamide, hydroxymethyl acrylamide, a difunctional acrylate, a trifunctional acrylate, and a divinyl compound, the reaction temperature is 50°C~100°C, and the ratio of the mass of the cross-linking agent in the mixture to the mass of the base core monomer is 0.01~0.1.
[0018] In a third aspect, the present invention provides a battery separator, wherein the polymer glue described in the first aspect and / or the polymer glue prepared by the preparation method described in the second aspect is evenly mixed with ceramic particles to obtain a mixed membrane liquid, and the mixed membrane liquid is coated on the surface of the separator substrate to obtain the battery separator.
[0019] In a fourth aspect, the present invention provides a battery comprising a positive electrode, a negative electrode, and the battery separator according to the third aspect located between the positive electrode and the negative electrode.
[0020] The polymer glue for diaphragm coating of the present invention comprises polymer particles, the polymer particles comprise an inner core and an outer shell coated on the inner core surface, the inner core comprises a base core having at least a surface with holes and an elastic structure in the holes at least penetrating the surface of the base core, the polymer particles have a PDI of less than 1, a uniform particle size and a D50 of 1 μm to 11 μm, and can avoid the polymer glue from filling gaps such as ceramic particles and diaphragm pores, reduce the internal resistance of conductive ions, and thus improve the rate and cycle performance of the battery, and the outer shell material is hot pressed under the conditions of 55° C. and 4 MPa, and the bonding force to the pole piece is not less than 5N / m, can improve the bonding strength of the polymer glue and promote the stable bonding between the coating and the electrode. The elastic modulus of the elastic structure material is 10MPa~80MPa, so that the ceramic coating can fully release the stress when the volume changes during the battery ion extraction and embedding process. It can ensure that the ceramic coating has a lasting bonding strength to the electrode and prevent the ceramic coating from falling off. The glass transition temperature of the core material is not less than 50℃, which provides rigidity for the polymer glue and can ensure the structural stability of the diaphragm. It can withstand a certain pressure without deformation during the battery manufacturing process, ensuring support and isolation for the electrode and the diaphragm.
[0021] Compared with the elastic structure directly coated on the surface of the base core to form the inner core, the elastic structure of the present invention runs through the holes on the surface of the base core, which can avoid the generation of a slip layer between the base core material and the elastic material during hot pressing, volume expansion and contraction, and high and low temperature cycles during the use of the battery, which affects the battery performance. The elastic structure runs through the holes on the surface of the base core to form elastic protrusions on the surface of the inner core, and can also lock the outer shell viscous material to avoid the generation of a slip layer between the inner core and the outer shell viscous material to affect the battery performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 The figure is a process flow chart of the method for preparing the polymer glue of the present invention.
[0024] Figure 2 It is a schematic diagram of product molding of the polymer glue of the present invention.
[0025] Figure 3 This is a scanning electron microscope photograph of the base core precursor of Example 1 of the present invention.
[0026] Figure 4 This is a scanning electron microscope photograph of the porous core of Example 1 of the present invention.
[0027] Figure 5 This is a scanning electron microscope photograph of the polymer particles of Example 1 of the present invention.
[0028] Figure 6 This is a scanning electron microscope photograph of the film-forming polymer glue of Example 1 of the present invention.
[0029] Figure 7 This is a particle size distribution diagram of the polymer particles of the polymer glue of Example 1 of the present invention.
[0030] Figure 8 Schematic diagram of the battery separator of the present invention. DETAILED DESCRIPTION
[0031] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0032] The inventors of the present application have found that existing ceramic coatings are difficult to release stress, are prone to powdering, and ceramic coating binders are prone to filling the gaps between ceramic particles and the pores of the diaphragm, affecting the rate and cycle performance of the battery.
[0033] In this regard, in the first aspect, the present invention provides a polymer glue for diaphragm coating, which includes polymer particles, the polymer particles include an inner core and an outer shell, the inner core includes a base core and an elastic structure, the base core has holes on at least the surface, the elastic structure at least penetrates the holes on the surface of the base core, the outer shell is coated on the surface of the inner core, the polymer particles have a PDI of less than 1 and a D50 of 1 μm~11 μm, the glass transition temperature of the material of the base core is not less than 50°C, the elastic modulus of the material of the elastic structure is 10 MPa~80 MPa, and the material of the outer shell is hot pressed under the conditions of 55°C and 4 MPa, and the bonding force to the electrode is not less than 5 N / m.
[0034] The polymer glue for the diaphragm coating of the present invention comprises polymer particles, the polymer particles comprise a core and a shell coated on the surface of the core, the core comprises a base core with at least a hole on the surface and an elastic structure at least penetrating the holes on the surface of the base core, the elastic structure of the present invention penetrates the holes on the surface of the base core, on the one hand, the elastic material is embedded in the base core material, which can avoid the generation of a slip layer between the base core material and the elastic material, on the other hand, an elastic protrusion is formed on the surface of the core, which can lock the shell material and avoid the generation of a slip layer between the core and the shell material. The elastic structure of the present invention penetrates the holes on the surface of the base core, and during hot pressing and battery use, no slip layer is generated between the rigid base core, the elastic material and the shell viscous material, and the combination is tight, which can keep the battery performance stable.
[0035] The polymer particles of the polymer glue of the present invention have a glass transition temperature of the core material of not less than 50° C., which provides rigidity for the polymer glue and can ensure the structural stability of the diaphragm. During the battery manufacturing process, it can withstand a certain pressure without deformation, ensuring support and isolation for the electrode and the diaphragm. The material of the shell is hot-pressed under the conditions of 55° C. and 4 MPa, and the bonding force to the electrode is not less than 5 N / m, which can improve the bonding strength of the polymer glue and promote stable bonding between the coating and the electrode. The elastic modulus of the material of the elastic structure is 10 MPa~80 MPa, which improves the rebound characteristics and flexibility of the ceramic coating, etc., so that the ceramic coating, etc. can fully release stress when the volume changes during the battery ion de-embedding process, and can ensure that the ceramic coating, etc. has a lasting bonding strength to the electrode, and prevent the ceramic coating, etc. from falling off.
[0036] The present invention uses a base core with a glass transition temperature of not less than 50°C, an elastic structure with an elastic modulus of 10MPa to 80MPa, hot pressing at 55°C and 4MPa, and a shell material with a bonding force to the electrode of not less than 5N / m. While ensuring that the ceramic coating and the like have a lasting bonding strength to the electrode and preventing the ceramic coating and the like from falling off, the structural stability of the diaphragm is ensured, and the support and isolation of the electrode and the diaphragm are ensured. The elastic structure runs through the holes on the surface of the base core, so that the rigid base core, the elastic material and the shell viscous material are tightly bonded, the battery performance is kept stable, and the role of ensuring lasting bonding strength and structural stability is maximized.
[0037] The polymer particles of the polymer glue of the present invention have a PDI of less than 1, a uniform particle size and a D50 of 1 μm to 11 μm, which can prevent the polymer glue from filling gaps between ceramic particles and diaphragm pores, reduce the internal resistance of conductive ions, and thus improve the rate and cycle performance of the battery.
[0038] In the present invention, if the elastic structure is directly coated on the surface of the base core to form the inner core, it is easy to cause the base core, the elastic material layer, and the outer shell to slip and lose adhesion during hot pressing, volume expansion and contraction during battery use, and high and low temperature cycles, affecting the stability of battery performance. In the present invention, if the PDI of the polymer particles is ≥1 and D50 is <1μm, it is easy to cause the problem of polymer glue filling gaps such as ceramic particles and diaphragm pores. If the polymer particles D50 is >11μm, it is easy to cause the distance between the diaphragm and the electrode to be too large. When the conductive ions are transmitted in the electrolyte, the ion conduction path becomes longer. According to the resistance law, the longer path leads to increased resistance, thereby increasing the internal resistance of the battery. The increase in the internal resistance of the battery further causes the energy loss of the battery to increase during the charge and discharge process, reducing the charge and discharge efficiency of the battery, and reducing the actual available capacity of the battery. If the elastic modulus of the elastic material of the elastic structure is >80MPa, it is easy to produce a ceramic coating. When the volume changes during the battery ion extraction and embedding process, the stress cannot be fully released, and the ceramic coating may lose powder. If the elastic modulus of the elastic material of the elastic structure is less than 10MPa, it is easy for the polymer glue to have insufficient support and binding force on the ceramic particles, making it difficult to resist the stress caused by the volume change of the electrode material, and it cannot return to its original state after being subjected to force. As the charge and discharge cycle proceeds, the electrode material may easily fall off the electrode sheet, resulting in a reduction in the active substance of the electrode, a decrease in the capacity of the battery, and poor charge and discharge performance. If the bonding force of the outer shell material to the electrode sheet is less than 5N / m, it is easy for the bonding force between the coating and the electrode sheet to deteriorate, and the ceramic coating may lose powder.
[0039] The PDI of the polymer particles is preferably <0.3, more preferably <0.1, and further preferably <0.05. The D50 is, for example, 1μm, 3μm, 5μm, 7μm, 9μm and 11μm. The elastic modulus of the material of the elastic structure is, for example, 10MPa, 20MPa, 30MPa, 40MPa, 50MPa, 60MPa, 70MPa and 80MPa.
[0040] In some preferred embodiments, the base core is a porous base core, and the elastic structure penetrates through the pores inside the porous base core. Under this preferred embodiment, the base core is a porous base core. Since the porous structure provides additional support, it is more conducive to improving the mechanical strength and puncture resistance of the diaphragm, and avoiding physical damage to the diaphragm during battery assembly and use. The porous structure helps to disperse heat and reduce the risk of thermal runaway, which is more conducive to improving the thermal stability of the diaphragm and improving safety. Since the porous structure increases the specific surface area of the diaphragm, it is more conducive to improving the adsorption and retention capacity of the diaphragm for the electrolyte. Since the porous structure improves the wettability of the diaphragm with the electrolyte, it is more conducive to the uniform distribution of the electrolyte in the battery and improves the battery performance. Since the porous structure provides more ion transmission channels, it is more conducive to improving the ion conductivity of the diaphragm, reducing the internal resistance of the battery and improving the battery performance. The base core is a porous base core, and the pores inside the porous base core are penetrated by an elastic structure, which is more conducive to avoiding the generation of a slip layer between the base core material and the elastic material during hot pressing and volume expansion and contraction during the use of the battery, and high and low temperature cycles that affect the stability of the battery performance.
[0041] In some preferred embodiments, in the inner core, the volume ratio of the elastic structure to the base core is 1:2.5~9. Under this preferred solution, it is more conducive to ensuring that the rigid base core effectively supports the pole piece so that it does not collapse during hot pressing, ensuring the structural stability of the diaphragm, ensuring the support and isolation of the pole piece and the diaphragm, ensuring that the ceramic coating and the like fully release stress when the volume changes during the battery ion extraction and insertion process, ensuring that the ceramic coating and the like have a lasting bonding strength to the pole piece, and at the same time, it is more conducive to effectively locking the shell viscous material through the elastic protrusions on the surface of the inner core, avoiding the formation of a slip layer between the inner core and the shell viscous material, and maintaining stable battery performance. In the inner core, the volume ratio of the elastic structure to the base core is, for example, 1:2.5, 1:4, 1:7 and 1:9.
[0042] In some preferred embodiments, in the polymer particles, the volume ratio of the shell to the base core is 1:1.5-6. Under this preferred embodiment, it is more conducive to ensuring that the rigid base core effectively supports the pole piece so that it does not collapse during hot pressing, ensuring the structural stability of the diaphragm, ensuring the support and isolation of the pole piece and the diaphragm, and more conducive to improving the bonding strength of the polymer glue and promoting the stable bonding of the coating and the pole piece. In the polymer particles, the volume ratio of the shell to the base core is, for example, 1:1.5, 1:2, 1:3, 1:4, 1:5 and 1:6.
[0043] In some preferred embodiments, the base core comprises a polymer formed by polymerization of a base core monomer, and the base core monomer comprises at least one of an acrylic monomer and a vinyl monomer. Specifically, the acrylic monomer may comprise a methacrylic monomer, for example.
[0044] Preferably, the base core includes polymethyl methacrylate (PMMA). In this preferred embodiment, PMMA does not contain a benzene structure, which is in line with the environmental protection concept of battery development and ensures that the battery manufacturing and subsequent recycling are more friendly and healthy to the ecological environment.
[0045] In some preferred embodiments, the shell comprises a copolymer, and the copolymer is formed by copolymerization of a mixed monomer comprising a first shell monomer, a second shell monomer, and a third shell monomer, wherein the first shell monomer is selected from at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, lauryl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, and vinyl acetate, and the second shell monomer is selected from at least one of trifluoroethyl methacrylate, 2-hydroxyethyl methacrylate, and 1,2-difluoroethyl methacrylate. At least one of 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, ethylene glycol diacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, glycidyl methacrylate, N-hydroxymethyl acrylamide, N-butoxymethyl acrylamide, divinylbenzene, vinyl trimethoxysilane, and γ-methacryloxypropyl trimethoxysilane, and the third shell monomer is selected from at least one of methyl methacrylate, ethyl methacrylate, methacrylic acid, acrylic acid, acrylonitrile, styrene, isobornyl methacrylate, and acrylamide. Under this preferred embodiment, the copolymer of the shell is formed by copolymerization of the first shell monomer, the second shell monomer, and the third shell monomer. The first shell monomer mainly provides viscosity, the second shell monomer mainly provides cross-linking structure and functional groups, and the third shell monomer mainly improves the viscosity strength, which is more conducive to improving the bonding strength of the polymer glue and promoting the stable bonding of the coating and the pole piece; the participation of the second shell monomer in the copolymerization can also improve the electrolyte resistance and bonding performance of the ceramic coating. Further preferably, the mass ratio of the first shell monomer, the second shell monomer, and the third shell monomer is 1:0.06~2:0.3~4, which is more conducive to improving the bonding strength of the polymer glue and promoting stable bonding between the coating and the electrode.
[0046] In some preferred embodiments, the material of the elastic structure is a monofunctional acrylate oligomer.
[0047] In some preferred embodiments, the viscosity of the polymer glue is preferably 10 cps to 1000 cps, and the solid content is preferably 1 wt % to 80 wt %.
[0048] In a second aspect, the present invention provides a method for preparing the polymer glue according to the first aspect, referring to Figure 1 , including: preparing a spherical base core precursor, the glass transition temperature of the material of the base core precursor is not less than 50°C, making holes on at least the surface of the base core precursor to obtain a base core, the base core at least has holes on the surface, so that an elastic material at least penetrates the holes on the surface of the base core to obtain an inner core, the elastic modulus of the elastic material is 10MPa~80MPa, coating the surface of the inner core with a viscous material, preparing a stable emulsion to obtain the polymer glue, the viscous material is hot pressed under the conditions of 55°C and 4MPa, and the bonding force to the electrode is not less than 5N / m.
[0049] In some preferred embodiments, the preparation of the base core comprises: emulsifying and mixing a mixture including the base core precursor, a porogen, a water-soluble monomer, an initiator, an emulsifier, and water, reacting under stirring conditions, washing with water, and solid-liquid separation to obtain the base core, the porogen is selected from at least one of cyclohexanol, toluene, xylene, benzene, acetone, isopropanol, ethyl acetate, and halogenated hydrocarbons, the water-soluble monomer is selected from at least one of acrylic acid, methacrylic acid, acrylamide, methacrylamide, N,N-dimethylacrylamide, and propenyl ether, the reaction temperature is 55° C. to 100° C., the reaction time is 2 h to 10 h, and the mass ratio of the base core precursor, the porogen, and the water-soluble monomer in the mixture is 1:0.01~0.27:0.01~0.45; The preparation of the inner core comprises: emulsifying and mixing a mixture comprising the base core, an elastic material, an emulsifier and water uniformly to obtain the inner core, wherein the mass ratio of the elastic material to the base core in the mixture is 1:1.5-12.
[0050] Under this preferred embodiment, the porogen introduces the water-soluble monomer into the base core precursor, and the water-soluble monomer is separated during the water washing process to obtain the base core, the porogen is selected from at least one of cyclohexanol, toluene, xylene, benzene, acetone, isopropanol, ethyl acetate, and halogenated hydrocarbons, the water-soluble monomer is selected from at least one of acrylic acid, methacrylic acid, acrylamide, methacrylamide, N,N-dimethylacrylamide, and propenyl ether, the reaction temperature is 55°C~100°C, the reaction time is 2h~10h, the mass ratio of the base core precursor, the porogen, and the water-soluble monomer is 1:0.01~0.27:0.01~0.45, which is more conducive to forming pores in the base core precursor to obtain a porous base core, and further, in the process of emulsifying and mixing the mixture including the base core, the elastic material, the emulsifier, and water, the elastic material penetrates the pores of the base core, and the mass ratio of the elastic material to the porous base core is 1:1.5~12, which is more conducive to the elastic material penetrating the pores inside the porous base core. The mass ratio of the elastic material to the base core in the mixture is, for example, 1:1.5, 1:3.5, 1:6, 1:8, 1:10 and 1:12.
[0051] Preparation of the base core, the initiator is, for example, one or more of dibenzoyl peroxide, dilauroyl peroxide, di-tert-butyl peroxide, diisopropylbenzene peroxide, azobisisobutyronitrile, azobisisoheptylnitrile, potassium persulfate, sodium persulfate, and ammonium persulfate, the emulsifier is, for example, one or more of nonionic surfactants and anionic surfactants, and the effective ingredients other than water are preferably 56wt% to 96.85wt% by weight of the base core precursor, 1wt% to 15wt% by weight of the porogen, 1wt% to 25wt% by weight of the water-soluble monomer, 0.15wt% to 1wt% by weight of the initiator, and 1wt% to 3wt% by weight of the emulsifier. Preparation of the core, the emulsifier is, for example, one or more of nonionic surfactants and anionic surfactants.
[0052] In some preferred embodiments, the preparation of the inner core comprises: emulsifying and mixing a mixture comprising the base core, an elastic material, an emulsifier, and water to obtain the inner core, wherein the mass ratio of the elastic material to the base core in the mixture is 1:2.5-9. Under this preferred embodiment, it is more advantageous to make the volume ratio of the elastic structure to the base core in the inner core be 1:2.5-9. The emulsifier is, for example, one or more of a nonionic surfactant and an anionic surfactant. The mass ratio of the elastic material to the base core in the mixture is, for example, 1:2.5, 1:4, 1:7, and 1:9.
[0053] In some preferred embodiments, the coating of the viscous material comprises: emulsifying and mixing a mixture including the core, an initiator, an emulsifier, and a viscous material monomer uniformly, and coating the viscous material on the surface of the core by polymerization reaction, and the mass ratio of the viscous material monomer to the base core is 1:1.5~6. Under this preferred embodiment, the mass ratio of the viscous material monomer to the base core is 1:1.5~6, which is more conducive to the polymer particles, and the volume ratio of the shell to the base core is 1:1.5~6. The initiator is, for example, one or more of an organic peroxide, an inorganic peroxide, an azo or a redox initiator, the reaction temperature is preferably 50°C~120°C, and the reaction time is preferably 0.5h~24h. The mass ratio of the viscous material monomer to the base core is, for example, 1:1.5, 1:2, 1:3, 1:4, 1:5 and 1:6.
[0054] In some preferred embodiments, the preparation of the base core precursor includes: mixing a mixture including a dispersant, an emulsifier, a base core monomer, an initiator, and a cross-linking agent in water, and separating the solid and liquid after the reaction to obtain the base core precursor, wherein the cross-linking agent is selected from at least one of acrylamide, hydroxymethyl acrylamide, a difunctional acrylate, a trifunctional acrylate, and a divinyl compound, the reaction temperature is 50°C~100°C, and the ratio of the mass of the cross-linking agent in the mixture to the mass of the base core monomer is 0.01~0.1.
[0055] Under this preferred embodiment, in the preparation of the base core precursor, the crosslinking agent is selected from at least one of acrylamide, hydroxymethyl acrylamide, difunctional acrylate, trifunctional acrylate, and divinyl compounds, the reaction temperature is 50°C to 100°C, and the ratio of the mass of the crosslinking agent to the mass of the base core monomer is 0.01 to 0.1, which is more conducive to ensuring that the base core monomer forms a uniform network structure during the polymerization process, maintaining the integrity of the sphere, preventing the base core precursor from breaking or deforming during the polymerization process, improving the structural stability of the base core precursor, preventing the spherical structure from collapsing during the base core precursor pore preparation process, preventing the pore structure from collapsing or deforming during use as a battery separator coating glue, ensuring the long-term stability of the pore structure, and improving the base core precursor The pore-forming effect of preparing the base core. The ratio of the mass of the crosslinking agent in the mixture to the mass of the base core monomer is, for example, 0.01, 0.03, 0.05, 0.07, 0.09 and 1.
[0056] The dispersant is selected from one or more of polyacrylic acid, carboxymethyl cellulose and its salt, polyvinyl alcohol, polyvinyl pyrrolidone, and polyacrylamide, the emulsifier is selected from one or more of polyoxyethylene ether, ethylene oxide and propylene oxide copolymer, polybasic fatty acid ester, alkyl sulfate, alkyl benzene sulfonate, and quaternary ammonium salt, the base core monomer is selected from one or more of acrylic acid, methacrylic acid, and vinyl monomers, preferably methyl methacrylate (MMA) monomer, the initiator is selected from one or more of dibenzoyl peroxide, dilauroyl peroxide, di-tert-butyl peroxide, dicumyl peroxide, azobisisobutyronitrile, azobisisoheptylnitrile, potassium persulfate, sodium persulfate, and ammonium persulfate, and the reaction time is, for example, 1h to 12h. Excluding the effective ingredients other than water, the mass proportion of the dispersant is preferably 1wt% to 15wt%, the mass proportion of the emulsifier is preferably 1wt% to 3wt%, the mass proportion of the initiator is preferably 0.3wt% to 1wt%, the mass proportion of the crosslinker is preferably 1wt% to 6wt%, and the mass proportion of the base core monomer is preferably 75wt% to 96.7wt%. When the base monomer is an acrylic monomer or a vinyl monomer, the polymerization reaction rate and degree of polymerization are easier to control, which is more conducive to accurately controlling the progress of the polymerization reaction and obtaining spherical particles with uniform particle size and regular morphology. When the base monomer is a methyl methacrylate (MMA) monomer, it has more suitable reaction activity and is more conducive to the smooth occurrence of free radical polymerization reaction under the action of the initiator, accurately controlling the polymerization process and obtaining spherical particles with uniform particle size and regular morphology.
[0057] In a third aspect, the present invention provides a battery separator, referring to Figure 8 , the polymer glue described in the first aspect and / or the polymer glue prepared by the preparation method described in the second aspect are mixed evenly with ceramic particles to obtain a mixed membrane liquid, and the mixed membrane liquid is applied to the surface of the diaphragm substrate to obtain the battery diaphragm. The battery diaphragm of the present invention has a ceramic heat-resistant coating, the polymer glue is not easy to fill the gaps between ceramic particles and the pores of the diaphragm, the battery has high rate and cycle performance, can fully release stress when the volume changes during the battery ion extraction and insertion process, has a lasting bonding strength to the pole piece, and is not easy to fall off.
[0058] In a fourth aspect, the present invention provides a battery comprising a positive electrode, a negative electrode, and the battery separator according to the third aspect located between the positive electrode and the negative electrode.
[0059] The present invention is further described in detail below with reference to specific embodiments.
[0060] Example 1 A method for preparing a polymer glue for a diaphragm coating, referring to Figure 2 , the steps are as follows: Step 1: Add 200 parts of deionized water, 6 parts of polyvinyl alcohol (dispersant), 1 part of OP-10 (dodecylphenol polyoxyethylene ether, emulsifier) to the reactor, stir evenly, then add 90 parts of methyl methacrylate (core monomer), 0.5 parts of azobisisobutyronitrile (initiator), 3 parts of 1,6-ethylene glycol diacrylate (cross-linker, difunctional acrylate) and mix evenly, heat to 70°C, react for 8 hours, filter (solid-liquid separation) to obtain the core precursor, wherein the aforementioned parts refer to the mass, and among the effective ingredients other than deionized water, the mass proportion of the dispersant is 5.97wt%, the mass proportion of the emulsifier is 1wt%, the mass proportion of the core monomer is 89.6wt%, the mass proportion of the initiator is 0.5wt%, the mass proportion of the cross-linker is 2.99wt%, and the ratio of the mass of the cross-linker to the mass of the core monomer is 0.033; the scanning electron microscope photo of the core precursor is referenced Figure 3 ; Step 2: 75 parts of the base core precursor prepared in step 1 are emulsified and mixed with 15 parts of cyclohexanol (porogen), 10 parts of acrylamide (water-soluble monomer), 0.15 parts of ammonium persulfate (initiator), and 2 parts of polyvinyl pyrrolidone (emulsifier) in 200 parts of deionized water, and then heated to 65°C for reaction for 5 hours under stirring, discharged, washed with water, and solid-liquid separation is performed to obtain the base core, wherein the aforementioned parts refer to mass, and among the effective ingredients other than deionized water, the mass proportion of the base core precursor is 73.4wt%, the mass proportion of the porogen is 14.68wt%, the mass proportion of the water-soluble monomer is 9.79wt%, the mass proportion of the initiator is 0.15wt%, and the mass proportion of the emulsifier is 1.96wt%. The mass ratio of the base core precursor, the porogen, and the water-soluble monomer is 1:0.2:0.13, and the base core is a porous base core; the scanning electron microscope photograph of the porous base core refers to Figure 4 ; Step 3: Emulsify and mix 50 parts of the base core prepared in step 2, 20 parts of monofunctional acrylate oligomer (elastic material) with elastic modulus E=40MPa, 0.5 parts of potassium persulfate (initiator), and 2.5 parts of polyoxyethylene polyoxypropylene ether (emulsifier) in 200 parts of deionized water, then heat to 75°C, add pre-emulsified emulsion mixed with 10 parts of n-butyl acrylate (first shell monomer), 4 parts of 2-hydroxyethyl methacrylate (second shell monomer) and 16 parts of methyl methacrylate (third shell monomer) into the reactor, mix evenly, react for 8 hours to end the reaction, adjust the viscosity and solid content to form a stable emulsion, i.e., polymer glue, the mass ratio of elastic material to base core is 1:2.5, the first shell monomer, the second shell monomer, and the third shell monomer are used as viscous material monomers, and the mass ratio of viscous material monomer to base core is 1:1.67.
[0061] A polymer glue for diaphragm coating is prepared by the above-mentioned preparation method, the polymer glue comprises polymer particles, the polymer particles comprise an inner core and an outer shell coated on the inner core surface, the inner core comprises a base core and an elastic structure, the base core is a porous base core, the elastic structure is penetrated through the pores on the surface of the porous base core and the pores inside the porous base core, the material of the elastic structure is a monofunctional acrylate oligomer, the elastic modulus of the material of the elastic structure is 40MPa, the material of the base core is polymethyl methacrylate (PMMA), the glass transition temperature of the material of the base core is 105°C, the material of the outer shell is n-butyl acrylate-2-hydroxyethyl methacrylate-methyl methacrylate copolymer, the material of the outer shell is hot pressed under the conditions of 55°C and 4MPa, the bonding force to the electrode is 8N / m, the PDI of the polymer particles is less than 1 and the D50 is about 5μm, and the particle size distribution diagram of the polymer particles can be seen in Figure 7 In the core, the volume ratio of the elastic structure to the porous core is 1:2.5, and in the polymer particles, the volume ratio of the shell to the core is 1:1.67. Figure 5 .
[0062] Example 2 The preparation method is carried out in accordance with Example 1, except that in step 1, the base core monomer is styrene, and the polymer glue used for the diaphragm coating in Example 1 is used, and the base core material is polystyrene (glass transition temperature is 100° C.).
[0063] Example 3 The preparation method is carried out in accordance with Example 1, except that in step one, the base core monomers are equal amounts of styrene and methyl methacrylate, and the polymer glue used for the diaphragm coating in Example 1 is used, and the base core material is a copolymer of styrene and methyl methacrylate (glass transition temperature is 102.5°C).
[0064] Example 4 The preparation method is carried out in accordance with Example 1, except that in step 2, the cyclohexanol porogen is replaced by n-heptane porogen; referring to the polymer glue used for the diaphragm coating in Example 1, the base core is a base core with holes on the surface, and the pores on the surface of the base core are penetrated by an elastic structure.
[0065] Example 5 The preparation method is carried out in accordance with that of Example 1, except that in step three, the amount of elastic material added is 4 parts, and the mass ratio of the elastic material to the base core is 1:12.5; referring to the polymer glue used for the diaphragm coating in Example 1, the pores on the surface of the porous base core are penetrated by an elastic structure, and in the inner core, the volume ratio of the elastic structure to the porous base core is 1:12.5.
[0066] Example 6 The preparation method is carried out in accordance with Example 1, except that in step three, the amount of elastic material added is 5 parts, and the mass ratio of the elastic material to the base core is 1:10; referring to the polymer glue used for the diaphragm coating in Example 1, in the inner core, the volume ratio of the elastic structure to the porous base core is 1:10.
[0067] Comparative Example 1 The preparation method is carried out in accordance with Example 1, except that step two is not performed; referring to the polymer glue for the diaphragm coating in Example 1, the polymer glue includes polymer particles, the polymer particles include a polymethyl methacrylate (PMMA) inner core, a first coating layer coated on the outside of the inner core, and a second coating layer coated on the outside of the first coating layer, the elastic modulus of the first coating layer is 40 MPa, the material of the first coating layer is a monofunctional acrylate oligomer, and the material of the second coating layer is a copolymer of n-butyl acrylate-2-hydroxyethyl methacrylate-methyl methacrylate.
[0068] Test Case The polymer glues of Examples 1 to 6 and Comparative Example 1 were respectively mixed with ceramic particles to obtain a mixed film solution, wherein the ceramic particles were aluminum oxide particles. The mixed film solution was coated on the surface of a PE material diaphragm substrate (single-sided coating, coating thickness of 5 μm) to obtain a battery diaphragm, wherein the surface of the battery diaphragm had a ceramic coating. The film-forming scanning electron microscope photo of the polymer glue of Example 1 is shown in FIG. Figure 6 . The initial bonding strength between the ceramic coating and the pole piece was tested. The pole piece was made of aluminum foil coated with ternary materials. The test method was to heat press the battery separator and the pole piece for 60s under 4MPa and 55℃ to prepare a test plate. The free end of the pole piece was folded 180° on the tensile testing machine, and the free end of the pole piece and the test plate were clamped on the upper and lower clamps respectively. The tensile testing machine was used to continuously peel at a certain tensile speed until the pole piece and the ceramic coating were completely separated. The peel strength test result was read as the initial bonding strength (GB / T 2790-1995). The results are shown in Table 1. The performance stability of lithium-ion batteries was tested. The battery separator was assembled into a lithium-ion battery, and the charge and discharge cycle was 400 times. The battery capacity retention rate was measured (GB / T 31484-2015). The results are shown in Table 1. For lithium-ion batteries, the change in the bonding strength between the ceramic coating and the pole piece after 400 cycles was tested (GB / T 2790-1995). The results are shown in Table 1.
[0069] Table 1
[0070] Compared with the embodiment and comparative example 1, the elastic structure penetrates the pores on the surface of the base core, which can improve the battery capacity retention rate and improve the performance stability of the lithium-ion battery.
[0071] Comparing Examples 1 to 3, the base core includes polymethyl methacrylate (PMMA), which is more conducive to improving the battery capacity retention rate and improving the performance stability of the lithium-ion battery. The base core is polymethyl methacrylate (PMMA), which is further more conducive to improving the battery capacity retention rate and improving the performance stability of the lithium-ion battery. Comparing Examples 1, 4 and 5, the base core is a porous base core, and the pores inside the porous base core are penetrated by the elastic structure, which is more conducive to improving the battery capacity retention rate and improving the performance stability of the lithium-ion battery. Comparing Examples 1 and 6, in the inner core, the volume ratio of the elastic structure to the base core is 1:2.5~9, which is more conducive to the ceramic coating having a lasting bonding strength to the electrode, improving the battery capacity retention rate, and improving the performance stability of the lithium-ion battery.
[0072] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A polymer glue for diaphragm coating, characterized in that: It includes polymer particles, which include a core and an outer shell. The inner core includes a base core and an elastic structure. The base core has holes on at least the surface, and the elastic structure at least penetrates the holes on the surface of the base core. The outer shell is coated on the surface of the inner core. The PDI of the polymer particles is less than 1 and the D50 is 1μm~11μm. The glass transition temperature of the material of the base core is not less than 50°C, the elastic modulus of the material of the elastic structure is 10MPa~80MPa, and the material of the outer shell is hot pressed under the conditions of 55°C and 4MPa, and the bonding force to the electrode is not less than 5N / m.
2. The polymer glue according to claim 1, characterized in that The base core is a porous base core, and the elastic structure penetrates through the pores inside the porous base core.
3. The polymer glue according to claim 1, characterized in that In the inner core, the volume ratio of the elastic structure to the base core is 1:2.5-9.
4. The polymer glue according to claim 1, characterized in that In the polymer particles, the volume ratio of the shell to the core is 1:1.5-6.
5. The polymer glue according to claim 1, characterized in that The base core includes a polymer formed by polymerizing a base core monomer, and the base core monomer includes at least one monomer selected from the group consisting of an acrylic monomer and a vinyl monomer.
6. The polymer glue according to claim 5, characterized in that The base core includes polymethyl methacrylate.
7. The polymer glue according to claim 1, characterized in that The shell comprises a copolymer, and the copolymer is formed by copolymerization of a mixed monomer including a first shell monomer, a second shell monomer, and a third shell monomer, wherein the first shell monomer is selected from at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, lauryl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, and vinyl acetate, and the second shell monomer is selected from at least one of trifluoroethyl methacrylate, 2-hydroxypropyl methacrylate, 1, At least one of 6-hexanediol diacrylate, tripropylene glycol diacrylate, ethylene glycol diacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, glycidyl methacrylate, N-hydroxymethyl acrylamide, N-butoxymethyl acrylamide, divinylbenzene, vinyl trimethoxy silane, and γ-methacryloxypropyl trimethoxy silane; and the third shell monomer is selected from at least one of methyl methacrylate, ethyl methacrylate, methacrylic acid, acrylic acid, acrylonitrile, styrene, isobornyl methacrylate, and acrylamide.
8. A method for preparing the polymer glue according to any one of claims 1 to 7, characterized in that: include: A spherical base core precursor is prepared, wherein the glass transition temperature of the material of the base core precursor is not less than 50°C, holes are formed at least on the surface of the base core precursor to obtain a base core, wherein the base core has holes on at least the surface, so that an elastic material at least penetrates through the holes on the surface of the base core to obtain an inner core, wherein the elastic modulus of the elastic material is 10MPa~80MPa, and a viscous material is coated on the surface of the inner core to prepare a stable emulsion to obtain the polymer glue, and the viscous material is hot pressed under the conditions of 55°C and 4MPa, and the bonding force to the electrode is not less than 5N / m.
9. The preparation method according to claim 8, characterized in that: The preparation of the base core comprises: emulsifying and mixing a mixture including the base core precursor, a porogen, a water-soluble monomer, an initiator, an emulsifier and water, reacting under stirring conditions, washing with water, and performing solid-liquid separation to obtain the base core, wherein the porogen is selected from at least one of cyclohexanol, toluene, xylene, benzene, acetone, isopropanol, ethyl acetate and halogenated hydrocarbons, and the water-soluble monomer is selected from at least one of acrylic acid, methacrylic acid, acrylamide, methacrylamide, N,N-dimethylacrylamide and propenyl ether, the reaction temperature is 55° C. to 100° C., the reaction time is 2 h to 10 h, and the mass ratio of the base core precursor, the porogen and the water-soluble monomer in the mixture is 1:0.01-0.27:0.01-0.45; The preparation of the inner core comprises: emulsifying and mixing a mixture comprising the base core, an elastic material, an emulsifier and water uniformly to obtain the inner core, wherein the mass ratio of the elastic material to the base core in the mixture is 1:1.5-12.
10. The preparation method according to claim 8, characterized in that: The preparation of the inner core comprises: emulsifying and mixing a mixture comprising the base core, an elastic material, an emulsifier and water uniformly to obtain the inner core, wherein the mass ratio of the elastic material to the base core in the mixture is 1:2.5-9.
11. The preparation method according to claim 8, characterized in that: The coating of the viscous material comprises: uniformly mixing a mixture including the core, an initiator and a viscous material monomer, and coating the viscous material on the surface of the core by polymerization reaction, wherein the mass ratio of the viscous material monomer to the base core is 1:1.5-6.
12. The preparation method according to claim 8, characterized in that: The preparation of the base core precursor comprises: uniformly mixing a mixture including a dispersant, an emulsifier, a base core monomer, an initiator and a cross-linking agent in water, and performing solid-liquid separation after the reaction to obtain the base core precursor, wherein the cross-linking agent is selected from at least one of acrylamide, hydroxymethyl acrylamide, a difunctional acrylate, a trifunctional acrylate and a divinyl compound, the reaction temperature is 50° C. to 100° C., and the ratio of the mass of the cross-linking agent in the mixture to the mass of the base core monomer is 0.01 to 0.
1.
13. A battery separator, characterized in that: The polymer glue described in any one of claims 1 to 7 and / or the polymer glue prepared by the preparation method described in any one of claims 8 to 12 are uniformly mixed with ceramic particles to obtain a mixed membrane liquid, and the mixed membrane liquid is applied to the surface of the diaphragm substrate to obtain the battery diaphragm.
14. A battery, characterized in that: The invention comprises a positive electrode, a negative electrode and the battery separator according to claim 13 located between the positive electrode and the negative electrode.
Citation Information
Patent Citations
Adhesive, preparation method thereof and slurry
CN114520329A
Composite negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery
CN117913233A
Secondary battery, preparation method thereof, electrode plate and electric device
CN118763227A
Cited By
Battery diaphragm, preparation method thereof and application of battery diaphragm in lithium ion battery
CN120221927A
Large-particle glue for diaphragm, diaphragm coating slurry, diaphragm and battery
CN121405843A